The implications of women's activity limitations and role disruptions during breast cancer survivorship. - Keesing, Sharon; Rosenwax, Lorna; McNamara, Beverley (Future Medicine, 2018)
Early survivorship is a time of critical transition for women survivors of breast cancer as they attempt to resume functional activities and important life roles. This study aimed to explore the challenges of women and their partners as they attempted to resume activities and roles, identify unmet needs and make recommendations regarding a suitable framework to support women and partners to recommence valued activities and important roles during early survivorship. Qualitative methods utilising in-depth interviews of women (n?=?18) and their partners (n?=?8), and two focus groups (n?=?10) were completed in Perth, Western Australia, between June 2014 and April 2015. These methods were used to facilitate women and partners' views regarding the resumption of previously meaningful activities and important life roles during early survivorship. Questions addressed their individual and shared experiences concerning self-care, leisure, social and productive activities and important roles. Thematic analysis was employed to determine themes. Women and partners reported significant impact on their ability to engage in valued activities, resulting in changes to participation in meaningful roles. Three themes were determined: (1) ambiguity regarding survivorship prevents resumption of activities and previous roles, (2) breast cancer continues to impact a couples' relationship during survivorship, and (3) support is needed to assist women and partners to resume activities and important roles. This research provides evidence suggesting that the ongoing symptoms of breast cancer treatment continue to impact many women and their partners, as they attempt to resume functional activities and important life roles during early survivorship. Disruption to these valued activities and roles may influence women and their partner's health and well-being during early survivorship and extend beyond this period. Rehabilitation following cessation of treatment could be offered as required to facilitate access to multi-disciplinary services and supports for both individuals and couples.